RECOMMENDATION OF DIPHTHERIA ANTITOXIN TO DIFFERENT SUSPECTS DURING THE DIPHTHERIA OUTBREAKS,LUMAJANG DISTRICT IN 2018 - Munif Arifin (Universitas Airlangga, 2020)
The number of diphtheria suspects in Lumajang district was the second highest in East Java province during the diphtheria outbreaks in 2018. The number of diphtheria cases was more than 500% in 2018 compared to 2017. To give diphtheria antitoxin (DAT), the provincial diphtheria expert team consider various suspects’ characteristics for DAT recommendation as DAT supplies are limited. This case report aimed to explore and describe the relationship between diphtheria suspects’ characteristics, including age, gender, symptoms, immunization status, duration of disease, and contact status with other suspects according to the DAT recommendations from the expert team. This case report was descriptive and used a cross-sectional approach. It was conductedduring the diphtheria outbreaks and involved total samples of all suspects. Based on age, the majority of the suspects (92%)were under 19 years old. Suspects at this age were the target of an outbreak response immunization (ORI) program. Those who were not targetted to receive ORI (aged over 19 years) began to appear in November and mostly in December. The trend of non-ORI targetted age increased after the third round of ORI implementation. According to the report form parents, most suspects (46.7%) had complete immunization status, and only 6.7% of their immunization records were reported on growth chart cards. All suspects with positive diphtheria never had and know routine immunization records. The laboratory tests show only 5% were suspected with positive diphtheria with a cultural type of mitis toxigenic. As many as 32% of the total suspects were recommended for DAT treatment. The use of controlled DAT could save 1,640,000 iU. Keywords: Diphtheria, outbreak response immunization, diphtheria antitoxin.